P008 Fracture liaison service management of patients aged 85 and older who sustain fragility fractures: audit and quality improvement. (23rd April 2022) - Appleyard, Thomas; Bethwaite, Kerrie; Dale, Nicky; Manning, Fay; Paskins, Zoe
Abstract: Background/Aims: Osteoporosis is a burdensome disease internationally, that is commonly diagnosed following fragility fracture. In line with national guidance, in 2018 the North Staffordshire Fracture Liaison Service (FLS) changed their management policy of patients aged ≥85 years who sustain fragility fractures. Instead of calling these patients for a dual-energy X-ray absorptiometry (DXA) scan, a letter was sent to the patient's General Practitioner, advising the empirical commencement of oral bisphosphonates. This audit aimed to evaluate whether the recommendations in this letter were enacted by GPs. Following audit, the text of the letter was changed, and a re-audit conducted to evaluate changes in practice. Methods: Patients aged ≥85 years sustaining a fragility fracture between December 2018 and October 2020 were identified from FLS records. Summary Care Records (SCRs) were used to identify whether each patient was receiving a bisphosphonate prescription at time of audit (October 2020). Analysis was descriptive, to report the proportion of patients prescribed a bisphosphonate. Quality improvement methodology informed changes to the standard letter, using GP feedback. Re-audit of fragility fractures occurring between December 2020 and May 2021 was undertaken in July 2021 to assess possible impact. Results: 408 eligible patients were identified in the initial audit, of which 79% were female. SCR data was available for 396 patients; median time between fracture and data collection was 9 months. 160 patients (40%) had a bisphosphonate prescribed as an acute or repeat prescription, of which >90% were alendronic acid. Following the first audit cycle, the letter was changed to address barriers to clinical decision-making including advice on relative contraindications and referral. 74 patient SCRs were reviewed in the 2 nd audit cycle (85% female) and 38 (51%) were recorded as prescribed a bisphosphonate (median time between fracture and assessment 5-months). Conclusion: Rates of bisphosphonate prescribing, in people aged ≥85 following a recommendation letter sent to the GP, have increased from 40% to 51% following quality improvement initiative. Furthermore, the proportion of patients prescribed a bisphosphonate is similar to previous national data in patients post-DXA. This is of interest, particularly given the de-prioritisation of non-communicable diseases during the COVID-19 pandemic, and demonstrates that an intervention which requires little time, can result in changes in practice. Limitations of this work include that the SCR only includes contemporaneous prescribing data so the period of time between drug recommendation and audit was different in 1 st and 2 nd cycles, meaning that adherence may be expected to be higher in the 2 nd cycle, because the period of time between letter and data collection was shorter, and not because of a change in our intervention. Disclosure: T. Appleyard: None. K. Bethwaite: None. N. Dale: None. F. Manning: None. Z. Paskins: None.